LEKSIKON KEBENCANAAN PADA MASYARAKAT DAYAK KANAYATN DI KECAMATAN MANDOR KABUPATEN LANDAK - Gamara, Jubilio Cesar; Wartiningsih, Agus; Syahrani, Agus (Universitas Tanjungpura, 2025)
In order to describe the inventory of the disaster lexicon in the Dayak Kanayatn community, the form of the disaster lingual units in the community, the meaning of the disaster lexicon in the Dayak Kanayatn community, and the plans for designing teaching modules as Indonesian language teaching materials in Junior High Schools (SMP), this research was carried out by analyzing the disaster lexicon in the Dayak Kanayatn community. A descriptive technique, which is a kind of qualitative research, is used. The Ahe language, which is used in Kanayatn Dayak daily speech and rituals, serves as the research's data source. Words (both monomorphemic and polymorphemic) and phrases serve as the research's data.. The techniques used are interviews, notes, recording and documentation. Data collection tools are a list of questions, writing tools, notebooks and gadgets. Based on the analysis carried out, there are 17 disaster lexicons and they are divided into 3 types, namely natural disasters with 7 words, non-natural disasters with 7 words and social disasters with 3 words.